2010
DOI: 10.1088/0022-3727/43/18/185301
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties and formation of a Schottky barrier at the CdS/PEDOT : PSS hybrid junction

Abstract: The behaviour of a hybrid heterojunction (HJ) of an inorganic semiconductor cadmium sulfide (CdS) single crystal (102 Ω cm) and an organic conducting polymer poly(3,4-ethylenedioxythiophene) : poly(styrene sulfonic acid) (PEDOT : PSS) has been studied using electrical and photoelectrical measurements as well as ultraviolet photoelectron spectroscopy (UPS) with in situ Ar ion etching. Photovoltaic data and current–voltage characteristics demonstrated that the HJ is a Schottky diode with an electron barrier heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Here, PEDOT:PSS was spin-coated onto the CdS NW networks by using its undiluted and diluted aqueous solutions. The p-type conductive polymer can not only form a uniform film with CdS NWs but can also easily form defect states because of disorder in its solid-state nanostructures, which is beneficial to electron–hole recombination. , As shown in Figure a,b, the devices with PEDOT:PSS (dilution ratio of 6:1) exhibit fast responses to light and ultrashort decay times in comparison with those without PEDOT:PSS. This fast response ability was further studied by using high time-resolved circuits in which an oscilloscope is placed in series with a photodetector at a frequency of 1000 Hz (Figures c and S6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, PEDOT:PSS was spin-coated onto the CdS NW networks by using its undiluted and diluted aqueous solutions. The p-type conductive polymer can not only form a uniform film with CdS NWs but can also easily form defect states because of disorder in its solid-state nanostructures, which is beneficial to electron–hole recombination. , As shown in Figure a,b, the devices with PEDOT:PSS (dilution ratio of 6:1) exhibit fast responses to light and ultrashort decay times in comparison with those without PEDOT:PSS. This fast response ability was further studied by using high time-resolved circuits in which an oscilloscope is placed in series with a photodetector at a frequency of 1000 Hz (Figures c and S6).…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the effect brought by PEDOT:PSS, which could be interpreted as the formation of a recombination mechanism similar to the effect of O 2 . Because a Schottky barrier is supposed to be formed at the PEDOT:PSS/CdS NW contact interface because of the energy level alignment (illustrated in Figure 5d), 35 the depletion region with low conductivity in CdS NWs also accounts for the drastic decrease of photocurrents in devices with undiluted PEDOT:PSS. The micromorphology of the hybrid film can be seen from the SEM image (Figure 5e).…”
Section: Methodsmentioning
confidence: 99%
“…This study confirmed that PEDOT:PSS itself does not play major role for rectifying J-V behaviors of ITO/CdS-PVA/PEDOT:PSS/ Al heterojunction. PEDOT:PSS is a hole conducting polymer with high electrical conductivity up to 200 S cm À 1 and often used in organic solar cells and light emitting diodes [34,35]. The addition of a thin PEDOT:PSS layer with ITO/CdS-PVA Schottky barrier, improves the hole transportation and protect back electron transfer from CdS-PVA to Al electrode which may increases the rectification ratio (5 times) and reduces leakage current.…”
Section: Resultsmentioning
confidence: 99%
“…Although the solar cells based on CdS nanocrystals usually do not demonstrate superior power conversion efficiency (PCE) (Table 1 ), this material is convenient to study as a proof of concept for new cell geometries and to model hybrid interface properties [ 4 , 14 16 ] due to the abovementioned advantages.…”
Section: Introductionmentioning
confidence: 99%